Anemia and Pregnancy: Therapeutic management with ferric polimaltosato. - Huamán Elera, José (2015)
A randomized trial was carry with 40 pregnants, that were being attended, in their second trimester, in the Prenatal Clinics of the MaternoPerinatal Institute (IMAPE). The first group received ferric hidrate polimaltose non ionic compund, in amount that equals 100 mg. of elemental iron, associated to 350 mg. of folic acid. After eigth weeks of treatment, when the patients were in their third trimester of pregnancy, were evaluated. The findings at this moment showed that hematic profile, of the pregnants that received iron, was signicatively better in relation to the control group. Only 2.3% of the patients presented intolerance to the substance used. On the basis of the general knowledge and the experience obtained with this study, a risk table for the anemia in pregnancy and a scheme for its treatment based on the figures obtained, for each level, are proposed.